2015
DOI: 10.4025/actascianimsci.v37i3.27069
|View full text |Cite
|
Sign up to set email alerts
|

<b>Comparative effects of dietary sea urchin shell powder and feed additives on meat quality and fatty acid profiles of broiler breast meat

Abstract: ABSTRACT. This study was a small pen trial in which we investigated comparative effects of dietary sea urchin shell powder and feed additives on meat quality and fatty acid profiles of broiler breast meat. A total of 108 male broilers were assigned to 3 groups (control, 1% sea urchin shell powder, and 1% feed additives) with 3 replicates of 12 chicks per pen in a completely randomized design for 28 days. The following parameters have been investigated: proximate composition (DM, CP, EE, and ash), physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Several studies have reported enhancing effects (Khaksefidi & Rahimi, 2005) and absent effects (Abdulla et al, 2017) of probiotics on the crude ash content of broiler meat. With regard to the effect of antioxidants on the ash content of broiler meat, Kim et al (2015) demonstrated that dietary supplementation with 1% sea urchin shell powder (rich in antioxidants) significantly reduced the ash content of broiler meat, whereas Marzoni et al (2014) and Rahman & Kim (2016) reported no effect of dietary natural antioxidant on ash content of meat from broiler chicks. The explanation for the lower ash content in the meat of AC-FCP broiler chicks in the current study therefore remains unelucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported enhancing effects (Khaksefidi & Rahimi, 2005) and absent effects (Abdulla et al, 2017) of probiotics on the crude ash content of broiler meat. With regard to the effect of antioxidants on the ash content of broiler meat, Kim et al (2015) demonstrated that dietary supplementation with 1% sea urchin shell powder (rich in antioxidants) significantly reduced the ash content of broiler meat, whereas Marzoni et al (2014) and Rahman & Kim (2016) reported no effect of dietary natural antioxidant on ash content of meat from broiler chicks. The explanation for the lower ash content in the meat of AC-FCP broiler chicks in the current study therefore remains unelucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activities of some phytogenics decrease the oxidative degradation of food by free radicals, favoring a longer shelf life (Koiyama et al, 2014). Chicken meat, compared to beef and pork, is more susceptible to lipid oxidation, as it has a higher proportion of polyunsaturated fatty acids in its composition, which originates free radicals and forms cholesterol oxides, changing the fatty acid composition and the production of volatile compounds (Kim, Chung, Chung, & Choi, 2015). For this reason, there is a growing interest in studies on phytogenic additives as potential natural antioxidants (Moraleco et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The market of sea urchin is particularly popular in countries like France, Ireland, Italy, Spain and Greece because of its distinctive aroma and very good taste (Kelly, 2005). South Korea has successfully tested the powder of sea urchin (Hemicentrotus pulcherrimus) shell, collected in local markets and used as a food supplement for broilers (Kim, Chung, Chung, & Choi, 2015).…”
Section: Introductionmentioning
confidence: 99%